Determining the nonlinear damping function using experiments - B. A. Kalashnikov; V. V. Bokhan; K. V. Penkov (Омский научный вестник)
In this article, the coefficients of the nonlinear damping function of a mechanical system with one translational degree of freedom are determined from an experimentally obtained oscillogram of free vibrations. The function is modeled using three types of damping: coulomb damping, linear viscous, and nonlinear viscous damping. Numerical values of the damping coefficients are identified. The characteristic of the dissipative force as a function of displacement is obtained, and is used to find the amount of energy dissipated over a time period. An equivalent relative damping ratio is approximated using the energy balance method and then used to perform numerical integration of the equation of motion. A satisfactory match of the envelope curve and the phase of the vibrational process is demonstrated by comparing the calculated oscillogram to the experimental one. The damping function parameters can be further refined by approximating the experimental amplitudes. The obtained value of the relative damping coefficient can be used to solve nonlinear problems in the area of dynamics of weakly damped systems.